Bio catalytic oxidation of sulphide laden wastewater from leather industry using sulfide: Quinone oxidoreductase immobilized bio reactor. Issue 2 (3rd March 2020) - Mannacharaju, Mahesh; Chittybabu, Sridevi; Sheikh John, Sardhar Basha; Somasundaram, Swarnalatha; Ganesan, Sekaran
Abstract: Anaerobic treatment of sulphate rich wastewater results in high amount of sulphide in liquid phase and gaseous phase. Sulphide is malodorous in gaseous phase and toxic even at very low concentrations in liquid phase and causes objectionable environmental issues. In the present investigation the sulphide present in the UASB treated post tanning wastewater was oxidised into elemental sulphur using Sulfide: Quinone oxidoreductase (SQR) immobilized Functionalized Carbon-silica matrix (FCSM) packed bed reactor. The variables employed for the production of Bacillus clausii biomass for the extraction of SQR were optimized using RSM. The purified SQR showed the maximum activity and stability at pH 6.0 to 8.0 and the percentage oxidation of sulphide at HRT of 24 h were 99.2% ± 0.2 at pH 6.0; 99.6% ± 0.2 at pH 7.0 and 99.6% ± 2.12 at pH 8.0. The effect of temperature on SQR activity was optimized and it established the maximum activity and stability at 40 °C with sulphide oxidation of 99.6% ± 0.8%. The optimum conditions for immobilization of SQR onto FCSM were time, 240 min; pH, 7.0; temperature, 40 °C and SQR concentration, 10 mg/g. The immobilization of SQR onto FCSM obeyed the Langmuir isotherm model. The immobilization of SQR onto FCSM was confirmed by SEM, FT-IR, XRD, TGA and DSC analyses. The SQR-FCSM packed bed reactor was operated separately for the oxidation of sulfide in UASB treated post-tanning wastewater under continuous mode at different HRTs and it recorded the maximum sulphide oxidation by 99 ± 0.1% at HRT of 15 h with residual sulphide of 2.4 ± 1.1 mg/L. The formation of elemental Sulphur was confirmed by XRD studies. The present investigation provides the scope for the removal of sulphide and thereby substantial reduction in Total Dissolved Solids from post tanning wastewater without addition of chemicals.